Portable thermoelectric cooler - Chew, Kelvin Zi Xun (Nanyang Technological University, 2023)
Over the years, fossil fuels are depleting rapidly and their use has caused severe environmental problems throughout the world. Industries are experimenting with different alternatives but there has not been any significant reduction in the reliance of fossil fuels. While industries play a major role in the consumption of fossil fuels, it is also the responsibility of households to lessen the burden. The largest contributor to energy usage at home is the cooling and heating system, such as air-conditioners and water heaters. In addition, air-conditioners contains refrigerants that releases huge amount of carbon into the environment. Carbon insulates our environment and plays a major role in global warming. Hence, the use of air-conditioners leads to a vicious cycle. The more we use air-conditioners, the more we will need them in the future. Hence, this project aims to develop a cooling system using thermoelectric coolers in place of refrigerants that provides cooling to individual users. With the use of thermoelectric coolers for personalized cooling, people will not need to use air-conditioners to cool the entire room when they are alone. Overall, the electricity consumption will also be lowered.